Parfane / Nur Farisah Nabilah Azhari … [et al.] - Azhari, Nur Farisah Nabilah; Adnan, Siti Syakirah; Kuu Shanorzie, Arieyana Dzulaiqha; Mohd Abdul Ghani, Mohd Ali Imran; Abd Azis, Rafidah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
To study the presented on how to keep the house in the fresh air condition. The company's goal is to keep our productivity at a reasonable cost while still maintaining a high-quality environment between management and employees. Parfane uses an automatic remote to turn the fan off and on, which can give benefits to customers because they won't have to use the stairs to replenish, and it'll be safer and easier to manage. Parfane can also benefit two in-one products, such as fans and fragrances, for a single fee.